Hjalmar Schiøtz, the great Norwegian innovator and his ophthalmoscope. (13th November 2013) - Keeler, C. Richard; Helland, Magne; Albert, Daniel M.
Abstract Recently, the authors encountered an intriguing and largely incomplete ophthalmoscope. The quest to identify and restore it led to a re‐evaluation of the evolution of the modern‐day ophthalmoscope and a re‐examination of the life and contributions of its inventor, the Norwegian ophthalmologist Hjalmar August Schiøtz.